A sin such as this [large type] - Hopkins, Ellen (Thorndike Press large print core series., 2018)
"In this gripping follow-up to Love Lies Beneath, beautiful, wealthy Tara Lattimore's story continues. For years, Tara suffered from the sins of others. She committed a few of her own. Now she wonders if the misdeeds of her past are about to catch up with her -- and derail her current marriage and her sanity."--Provided by publisher.